PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK ETAP) (Studi Kasus Pada CV. Citra Pandion Bernas di Kabupaten Solok) (JURNAL ECONOMICA : Research of Economic And Economic Education, 2013)
This research background overshadowed by presentation of CV Citra Pandion Bernas financial statement. Which is not required by ZAK of ETAP consist of balance, balance report, statement of changes in ekuitas, cash flow statement, and note of financial statement. While presented by financial statement is CV Citra Pandion Bernas only consisting of, profit report, capital statement and balance. Result of research indicate that CV.CITRA Pandion Bernas have applied its financial statement pursuant to ZAK of ETAP but not yet fully, still many element which not yet according to ZAK of ETAP, that is earnings which do not be dissociated pursuant to between operating income and earnings outside effort which is obtained. All purchasing of supply grouped in burden account at balance report, ought to supply when only which have used taken as burden that is equal to 70% from supply value. natural constraint by CV.CITRA Pandion Bernas in applying CV.CITRA Pandion Bernas among others, existence of mistake of conducted by calculation is CV.CITRA Pandion Bernas. There no division of clear duty between area because owner at the same time become organizer of[is effort. Owner also have other effort to be developed so that do not too focus at one area of is effort. Lack of human resource owning ability in compiling financial statement because do not in supporting with background education of accountancy.